KONTRIBUSI PEMIKIRAN BUSTHANUL ARIFIN TENTANG PELEMBAGAAN HUKUM ISLAM DAN PENINGKATAN WEWENANG PENGADILAN AGAMA DALAM SISTEM HUKUM NASIONAL - Tentiyo Suharto (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Indonesian national  law derived  from western law, customary law and Islamic law. Given the efforts to  establish the  institution  of Islamic  law  in Indonesia experienced many  challenges and  Religious  Courts institutions is still lacking in authority. Prof. Dr. H. Busthanul Arifin, SH continue to think seriously to make Islamic law as an integral part of the national  legal system. In the end, he can implement his ideals. Based on the above background of this study  revealed three  issues,  namely  First, Is Arifin Busthanul  contribute ideas  about  the institutionalization of Islamic  law in the  national  legal system.  Second, Is Arifin Busthanul  thinking  about  the authority of the Religious Courts in the national  legal system.  Third, How implications Arifin Busthanul  thinking on the institutionalization of Islamic law and  the authority  of the Religious Courts in the national  legal system to the development of Islamic law in Indonesia. The purpose of this study was  that Muslims know  the figures that played  a major  role behind the  enactment of Law Number.  7 Year 1989 regarding the  enactment of the Religious and Islamic Law Compilation  (KHI).Theoretical  studies in this research is the theory of the formation of the institutionalization of Islamic law, the theory of the relation  between religion and state  law and political theory. This research is a research study of character with the historical approach, the approach of the Act, the conceptual approach, and the comparative approach and data analysis techniques using inductive method. The results  of this study explains  that Islamic  law referred to and  determined by the legislation  can  apply directly without  going through  traditional  law,  the  Republic  of Indonesia (the  Government) can  set  something of a problem in accordance with Islamic  law, all the  settings  that apply only to the  followers  of Islam and  results Busthanul  Arifin contribute ideas  about  the  institutionalization of Islamic  law  are:  1. draft  Law on  Religious Courts, 2. draft Compilation  of Islamic  Law. Privileges Religious Courts under  Act Number.  3 2006 was  in the field of civil law include:  marriage, inheritance wills, grants,  endowments, alms,  charity, donation and  sharia economy. Implications of thought  Busthanul  Arifin against  the  Islamic  law in Indonesia is the  emergence  of legislation  that comes from Islamic  law, for example the  Law on Hajj, Zakat, Infak, Endowments, Economic Regulation  Based Regional Shari’ah and religion.